Orientalism in the narrative, music and myth of the amok in the 1937 film Zamboanga - Buenconsejo, Jose S. (2013)
Since the occupation of the Philippine Islands by the U.S. in 1899, Americans have viewed the Moslems of Mindanao as civilized yet aggressive. This orientalist-colonialist gaze is manifested in the film Zamboanga, a Filipino-American project directed by Filipino mestizo actor/director Eduardo de Castro, with a cast of Filipino "natives" and an Euro-American crew. A spectacle full of local color, Zamboanga has a narrative based on the cliched European trope, i.e., the abduction and recapture of the protagonist from the "seraglio". Contradicting this narrative, the original musical score by noted Hollywood composer Edward Kilenyi, Sr. is not Orientalist because it simply employed late-19th century romantic music conventionally used for such films, as well as the diegetic gong music accompanying Moslem war/martial dances. Yet, the intrusion into the film of musical sounds alien to the Zamboanga area, particularly the Hawaiian slack-key guitar and the Javanese pesindhen singing (normally accompanying a refined courtly dance), manifests musical Orientalism. These appropriations (perhaps by the director and producer) indicate the use of indexal sound icons as mere "signs of places" that disregard the specificities of cultural difference and local knowledge of Zamboanga and Sulu. The Hawaiian sound was meant to evoke the trope of a "tropical paradise" while the Javanese music depicted "Malay" civilization. Lastly, the myth of the amok is perpetuated to affirm an orientalist stereotype of the violent Moslem.